Dimensional compatibility of balloon‐tipped bronchial blockers with the pediatric airway anatomy using different recommendations for age‐related size selection. Issue 11 (13th September 2020) - Goetschi, Markus; Kemper, Michael; Dave, Mital H.; Kleine‐Brueggeney, Maren; Henze, Georg; Weiss, Markus
Abstract: Background: Age‐related recommendations for size selection of bronchial blocker devices are based on a few dated anatomical autopsy and radiological studies determining lower airway dimensions in children. These recommendations are based on anterior‐posterior internal bronchial diameters, which are smaller than the more relevant lateral internal bronchial diameters. Methods: Outer diameters of bronchial blocker balloons inflated with the maximum recommended volume of air were compared to age‐related lateral internal bronchial diameters of left and right proximal mainstem bronchi using five different recommendations for age‐related size selection of bronchial blocker equipment in children published in the literature. Results: The ratio of outer bronchial blocker diameters inflated with the maximal recommended volume of air to the median lateral internal diameters of the proximal mainstem bronchus ranged from 71.4% to 181.8% for the left side and from 61.7% to 162.6% for the right side. There were many settings where the blocker diameters did not reach the median lateral internal diameters of the proximal mainstem bronchus. This was more often observed for the right than for the left side (37 vs 22 settings). Conclusion: This analysis demonstrates that irrespective of the recommendation for size selection used, neither the two balloon‐tipped vascular catheters included nor the Arndt endobronchial blockers are ideal for lung isolation in children are compared with the age‐related relevant dimensions of pediatric airway anatomy. A redesign of bronchial blocker equipment with age‐related anatomically based high‐volume, low‐pressure blocker balloons made from ultrathin membranes and with smaller catheters would be desirable.